Pendidikan Kesehatan tentang Sumber Bahan Makanan Gizi Seimbang untuk Bayi dan Balita - Susanti, Ita (Nawadeepa: Jurnal Pengabdian Masyarakat, 2022)
The nutritional status of children greatly determines the quality of human resources. The nutritional status of children can be pursued trough the provision of balanced nutritional food intake to meet the needs of children in the process of growth and development. Selection of sources of balanced nutritional food is the basis for determining children’s intake, in order to meet children’s needs in the process of maintaining and repairing children’s body cells in supporting their growth and development process. In addition, the quality of balanced nutritional food intake is also influenced by the proper and proper management of food. The high incidence of stunting in children in Lam Batee Village shows the low knowledge of parents about balanced nutritional food sources in supporting the process of child growth and development. Therefore, this community service activity aims to provide health educational to the community about balanced nutritional food sources for infants and toddlers. The method of this activity is carried out with health education, questions and answers and discussions with pre-posttest designs. Before being given health education, participants were given a pre-test which aimed to measure parents’ knowledge about balanced nutritional food sources for infants and toddlers, then given health education. Participants who attended this activity were 24 parents who had children aged 6-59 months. Based on the post-test data, it showed that most of the parents had good knowledge, as much as 58,3%, compared to the pre-test data, where most of the parents had good knowledge, only 12,5%. It can be concluded that there was an increase in parental knowledge after being given health education about balanced nutritional food sources by 58,3%.